The Efficient Market Hypothesis and the Thinly Traded Kuala Lumpur Stock Exchange: Tests with Appropriate Refinements - Md Nassir, Annuar (1991)
Studies on the Efficient Market Hypothesis (EMH) in both the developed and developing capital markets have revealed mixed evidence. EMH presupposes an ability to detect incorrectly priced securities and profitable arbitraging opportunities which move the market towards efficiency. The early empirical work on developed securities markets purported to provide evidence that securities market prices are unbiased in their reaction to relevant information. This means that investors cannot consistently profit from any delays in price adjustment reflecting new information. However, evidence from subsequent studies, in the early 1980s, have not reached such cons is tent conclusion. These studies show anomalous price behaviour in securities markets: among others, size effects, turn of the year effects, week- end effects, etc., which are argued by some as evidence of market inefficiencies. The Kuala Lumpur Stock Exchange (KLSE) being small and illiquid provides a suitable setting to evaluate the EMH in a thinly traded scenario . In prior studies on market efficiency of the KLSE, no attempt was made to control for market thinness. In order to control for market thinness, ten portfolio deciles of KLSE listed stocks which differ in the degree of market thinness were created. The standardised volume of trading was proxied as a suitable indicator for measuring market thinness. Three tests were performed to evaluate the weak- form efficiency of the KLSE : (i) Q - statistic which measures the average serial correlations, (ii) individual serial correlations analysis (for 12 lags) and (iii) unit roots analysis. Test results on six equally-weighted dividend-distributed industry sector portfolios, two existing indices (namely the KLSE Composite Index and the New Straits Times (NST) Industrial Index) and an equally - weighted market ·portfolio (Rmt ) indicate that the KLSE Composite, the NST Indus trial and the two industry sec tors (hotel and tin sectors) exhibit average serial correlations cons is tent with weak- form efficiency. Results on the ten portfolios which differ on the degree of market thinness showed that all except three exhibit average serial correlations consistent with weak-form efficiency. For individual serial correlation results, 90 percent of the 30 component stocks of the NST Indus trial Index showed price behaviour consistent with random walk or weak- form efficiency. A unit root test was applied using a sample of stocks from each of the ten portfolio deciles. The Dickey-Fuller test of significance suggested that current prices are the best estimates of future prices. An average of 87 percent of the current price behaviour is explained by the immediate price lag variable. To evaluate the semi- strong form efficiency, an infrequently traded sample (Sample One) and a frequently traded sample (Sample Two) of annual earnings and dividend changes were used to study price react ions to information arrival. Three methods were used to estimate the residual returns: the market adjusted returns, the risk-adjusted returns and the risk-adjusted returns incorporating the Dimson, Fowler and Rorke (DFR) corrections for thin trading bias.